Professional Development for English Teachers in the Merdeka Curriculum: Needs and Challenges - Anis Setiyanti (Emanasi : Jurnal Ilmu Keislaman dan Sosial, 2024)
The implementation of the Merdeka Curriculum in Indonesia represents a significant shift toward flexible, student-centered learning that requires English teachers to continuously develop their pedagogical and professional competencies. As English plays a crucial role in global communication and education, teachers’ readiness to adapt to curriculum reform is essential. However, many teachers encounter challenges related to limited training opportunities, technological constraints, and institutional support. This study aims to examine the professional development needs and challenges faced by English teachers implementing the Merdeka Curriculum. A mixed-method research design was employed involving ten English as a Foreign Language (EFL) teachers from junior and senior high schools in Indonesia. Data were collected through questionnaires, semi-structured interviews, and classroom observations. Quantitative data were analyzed descriptively, while qualitative data were analyzed thematically to identify recurring patterns and contextual insights. The findings indicate that teachers demonstrate strong motivation for professional growth but require further support in project-based learning design, differentiated instruction, technology integration, and character education implementation. Key challenges include insufficient structured training, limited technological infrastructure, and heavy administrative workloads. Despite these constraints, teachers show positive attitudes toward curriculum reform and actively seek collaborative professional learning opportunities. The study underscores the importance of sustained, context-sensitive professional development programs, technological support, and institutional mentoring to ensure effective implementation of the Merdeka Curriculum and improve the quality of English language education in Indonesia.